Arka Noego obrazem Kościoła w "Enarrationes in psalmos" św. Augustyna - Zgraja, Brunon (Vox Patrum, 2016)
St. Augustine is regarded as master of the an allegorical interpretation of the Holy Scriptures. It consists in drawing out from the biblical text the deepest meaning. Using such kind of interpretation, he tried in one of his greatest exegetical works – Enarrationes in Psalmos, to explain for his faithful the mystery of the Church by means of a number of motives from the parables, biblical topographic and cosmic subjects, as well as from many biblical events and personages, interpreted in an allegorical spirit. So, in this article an effort has been made to show only some ideas of Augustine’s ecclesiological reflections that look as fruit of his allegorical interpretation of Noah’s Arc and the happenings related to it. The carried out analyses show that the figure of Noah’s Arc and the happenings related to it, served the bishop of Hippona to present the Church as a community composed of all nations of the world which are being incorporated in its organism after a previous conversion and receiving baptism as a result of proclamation the Gospel which should perform a priority role in the saving service of the Church. In Augustine’s opinion, the Church should be the place of proclamation the Truth, the teaching of which in the Church should be characterized by absolute fidelity to the Christian doctrine. What’s more, the Church is a community of saint and sinful people. It unceasingly undertakes strenuous efforts of moral cleaning, striving thereby for a growing moral perfection. That community is also characterized by awareness of a shared responsibility for the salvation of others, as well as by a conviction of the value of testifying to the holiness of life and the need of proclaiming the Word of God. These constitute an essential factor which mobilizes to a growing fidelity in fulfilling the will of God expressed in the commandments, and to undertaking a strenuous effort to proclaim the Gospel. The carried out analyses also allow to ascertain that the moral renewal undertaken by the members of the Church, should take place in accordance with the recommendations of Christ, and their progress in acquiring moral perfection does not remain without influence on perceiving the institution of the Church. Also obdurate sinners are members of the Church, those who, in spite of the words of encouragement addressed to them that they might start a way of fidelity to God, they put off the final decision of conversion, resigning in this way from the possibility of salvation, offered to them by God. The Church shown by means of an arc, is a Church unceasingly persecuted because it does not give consent to moral violations by the sinners, having a tolerating attitude toward them, in hope of their conversion. To Augustine’s vision of the Church belongs also his faithful safeguard of the Christian morality, as well as his fidelity in the service of proclaiming the Gospel. Both flow from the conviction of impossibility of one’s salvation outside the Church.